Representasi Kekerasan Emosional pada Perempuan dalam Film “Story of Kale: When Someone's In Love” - Wahab, Annisa Patricia; Juwita, Rina; Nurliah, Nurliah; Agustian, Jaka Farih (Universitas Batanghari Jambi, 2025)
This research aims to analyze the representation of emotional violence against women in the film